Usaha sama pelancongan desa - penilaian prinsip faedah bertanding mampan (sustainable competitive advantages): program homestay Tanjung Piai - Mohd. Latiff, Juraimi (2006)
Partnerships in the recent tourism industry is the main mechanism in developing competitive tourism destination as well as the rural tourism context. Based on the development of rural tourism in Malaysia since the past 20 years through Homestay Programme development. This program has been seen as the best approach in giving the added-value and value chain to the the rural traditional actvities. Therefore, based on the scenario, this study focuses on evaluating the level of rural tourism partnership in the principle of sustainable competitive advantages. The Lendrum Model of Strategic Partnerships (2003) which is the partnerships model in the manufacturing industrial context, is used as the basic theory for this study. Based on the theory, the literature review is the continues extend model which discussing the rural tourism context the finding of literature stated that partnership in rural tourism context is comprised of two forms of relationships which are public-private partnerships and cooperative networks. Tanjung Piai Homestay Programme is used as the case study to experiment the dimension using the weighted score. From the analysis, partnerships that focus on the two forms relationships is consider â€œvery lowâ€ which categoriesed in vendor segment. In the forms of public-private partnerships â€“ contract and tender in vendor segment. Therefore based on the situation the main limitation in rural tourism partnerships development in the sustainable competitive advantages which is comprised of eight main factors, [a] has no development strategic alliances; [b] has no longterm planning, [c]low mechanism in department coordination; [d] low focus in development; [e] has no competitive strategy; [f] profit oriented in tourism operator operation; [g] lack in initiative; dan [h] has no transperancy from tourism operator. From the finding this study has concluded four main mechanism to strengthen partnerships in the sustainable competitive advantage; [a] transformation or local organization structure; [b] management and coordination in public sector; [c] the guidelines and standard of industrial partnership; and [d] new partnerships development.